The heterogeneous roles of neutrophils in gastric cancer: scaffold or target? - Yansong Qin; Yunmei Liu; Peixin Dong; Wen-Bin Zou; Zhaoshen Li; Lei Huang (Cellular & Molecular Biology Letters)
Abstract Gastric cancer (GC) is a significant challenge for global health. Neutrophils, the predominant white blood cells in the innate immune system, are increasingly becoming known as potential contributors to either tumor-promoting or tumor-suppressive activities within different tumor biology settings. This review highlights such dual roles of neutrophils in GC, where complex interactions occur within the tumor microenvironment. Specifically, we focus on the formation and function of neutrophil extracellular traps (NETs), which have emerged as critical players in GC progression. NETs influence key processes such as inflammation, angiogenesis, and metastasis. This review offers a comprehensive analysis of the polarization of neutrophils into two of its distinct subtypes, namely N1 and N2, which exert opposing influences on tumor biology. While N1 neutrophils exert anti-tumor properties, N2 neutrophils are generally regarded as pro-tumor. We uniquely discuss how these subtypes interact with cancer cells, affecting epithelial–mesenchymal transition and immune evasion mechanisms. These interactions change the tumor microenvironment and impact overall GC progression. In addition, we underscore the potential of neutrophils and their associated molecules as biomarkers and therapeutic targets. Specific neutrophil-derived markers and neutrophil-associated signaling pathways, along with their perspectives in personalized medicine that would pave the way for neutrophil-based anti-GC therapy, have been discussed in this review. Through the integration of these perspectives, we aim to guide future research involving neutrophils and their therapeutic implications, thus establishing strategies to precisely and effectively treat GC and improve prognosis.